The Word “Sahib Awabad” According to Hadith Critics (Comparative Critical Study) - Al Azzam, Najah Mohammad (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: To identify the narrators labeled by hadith critics with terms such as "sahib awabid" (one with oddities) or its derivatives like "dhi awabid," or similar expressions, and to understand the critics’ intent behind using this term for them. Methods: The study followed an inductive-analytical approach, which involved tracking the narrators described by hadith critics as "sahib awabid" or its derivatives. Each narrator was then given a scientific biography according to the principles of al-jarh wa al-ta’dil (criticism and commendation). The study compared the statements of hadith critics about these narrators to determine their intended meaning of the term. Results: The number of narrators labeled by hadith critics as "sahib awabid" or its derivatives reached twenty-one. Out of these, four narrators were deemed slightly weak, fifteen were considered severely weak, and two narrators were subjects of disagreement among hadith critics. Conclusion: The term "sahib awabid" is a term of criticism used in hadith evaluation, often appearing in the form of a common saying. It was used for weak narrators with varying degrees of weakness. Therefore, the current study recommends conducting applied studies on the terms of criticism and commendation, especially those that appear as common sayings.